Privatization and structural adjustment in the Arab countries : papers presented at a seminar held in Abu Dhabi, United Arab Emirates, December 5-7, 1988 - El-Naggar, Saʻid, 1920-; Arab Monetary Fund; International Monetary Fund; United Nations Development Programme; United Nations. Economic and Social Commission for Western Asia ([Washington, D.C.] : International Monetary Fund, 1989)
This seminar volume, edited by Said El-Naggar, examines the challenge that Arab countries with large public sectors face in placing the privatization process within the wider context of structural change.
Includes bibliographical references.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Privatization -- Arab countries -- Congresses; Arab countries -- Economic policy -- Congresses; Structural adjustment (Economic policy) -- Arab countries -- Congresses; Arab countries -- Economic policy -- Congresses; Privatisation -- États arabes -- Congrès.; États arabes -- Politique économique -- Congrès.; Privatisation -- États arabes -- Congrès.; États arabes -- Politique économique -- Congrès.; Ajustement structurel (Économie) -- États arabes -- Congrès.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; Economic policy; Privatization; Structural adjustment (Economic policy); Arab countries; Privatisation -- Pays arabes -- Congrès.; Pays arabes -- Politique économique. -- Congrès.; Conference papers and proceedings